2013
DOI: 10.1080/02640414.2013.825729
|View full text |Cite
|
Sign up to set email alerts
|

Participation and performance trends in 100-km ultra-marathons worldwide

Abstract: The aims of the present study were to (1) investigate the participation trends for the origin of athletes competing in 100-km ultra-marathons and (2) determine the nationalities of athletes achieving the fastest 100-km race times worldwide. Race times and nationality from 112,283 athletes (15,204 women and 97,079 men) from 102 countries who completed a 100-km ultra-marathon worldwide between 1998 and 2011 were investigated using single-and multi-level regression analyses. The number of finishers increased expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
83
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 45 publications
(72 reference statements)
8
83
1
4
Order By: Relevance
“…This is not surprising since Europe is known for its flair for ultra-endurance events as they were leading in terms of participation in ultra-endurance disciplines such as 100km ultra-marathons (Cejka et al, 2013), multistage ultra-marathons (Shoak et al, 2013a) and in terms of participation and performance in 12-hour ultra-marathons (Sehovic et al, 2013), in 6-hour ultramarathons (Ehrensperger et al, 2013) as well as in ultra-triathlons . Furthermore, it is desirable to stay in the home country when deciding to participate in the first 161km ultra-marathon: "There is nothing worse than training for a race that is a few thousand miles from home, then showing up and laying an egg.…”
Section: Increasing Number Of Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not surprising since Europe is known for its flair for ultra-endurance events as they were leading in terms of participation in ultra-endurance disciplines such as 100km ultra-marathons (Cejka et al, 2013), multistage ultra-marathons (Shoak et al, 2013a) and in terms of participation and performance in 12-hour ultra-marathons (Sehovic et al, 2013), in 6-hour ultramarathons (Ehrensperger et al, 2013) as well as in ultra-triathlons . Furthermore, it is desirable to stay in the home country when deciding to participate in the first 161km ultra-marathon: "There is nothing worse than training for a race that is a few thousand miles from home, then showing up and laying an egg.…”
Section: Increasing Number Of Participantsmentioning
confidence: 99%
“…This is an interesting finding since Japanese athletes were dominating in terms of participation, and Japanese women in terms of participation and performance in the 'Spartathlon', an ultra-marathon held in Europe over a distance of 246 km . Furthermore, Japanese athletes were dominating in terms of performance in 100km ultra-marathons worldwide (Cejka et al, 2013). However, in 161km ultramarathons, only 162 finisher originated from Japan although the annual number of finishers from Japan increased from 14 (2010) …”
Section: Increasing Number Of Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased fluid intake during ultra-marathon running might also have negative effects on the feet since recent studies showed an association between fluid intake and limb swellings [71,72]. Fluid intake was related to the changes in limb volumes, where athletes with an increased fluid intake developed an increase in limb volumes [71].…”
Section: Exercise-associated Hyponatremia In Ultra-marathon Runningmentioning
confidence: 99%
“…Fluid intake was related to the changes in limb volumes, where athletes with an increased fluid intake developed an increase in limb volumes [71]. An increase in feet volume after a 100-km ultra-marathon was due to an increased fluid intake [72].…”
Section: Exercise-associated Hyponatremia In Ultra-marathon Runningmentioning
confidence: 99%